Amputation for osteomyelitis in a patient with spina bifida - Chui, Karen K M (J Surg Case Rep, 2018)
We describe a case of osteomyelitis in a patient with spina bifida presenting to the vascular surgeon and highlight the complex challenges encountered. We review the literature and demonstrate how good multidisciplinary care and early consideration for surgical amputation may benefit this unique group of patients.